Development, growth and finance of organizations from an Eastern European context : the 2015 Griffiths School of Management Annual Conference on Business, Entrepreneurship and Ethics (GSMAC) /: the 2015 Griffiths School of Management Annual Conference on Business, Entrepreneurship and Ethics (GSMAC). ([2017]) - Unknown
No abstract available